2012
DOI: 10.1097/ico.0b013e31823f8d3c
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Keratoconus in an Iranian Population

Abstract: The incidence of KCN in our context is apparent and comparable with rates in other studies on Asian ethnic populations. This is much higher than the incidence in European Caucasians and warrants further genetic and environmental studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
46
4
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 14 publications
(20 reference statements)
5
46
4
3
Order By: Relevance
“…Reported prevalence of KC in the literature was between 0.0004% and 0.2%. 11,[24][25][26][27][28] Reported prevalence of FMF ranges from 1:200 to 1:1000. 29 When we compared the prevalence of KC in the FMF group (4%) with the highest prevalence of KC reported in the literature 11 (0.2%), the prevalence of KC in the FMF group (4%) was still statistically significantly higher than that reported previously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported prevalence of KC in the literature was between 0.0004% and 0.2%. 11,[24][25][26][27][28] Reported prevalence of FMF ranges from 1:200 to 1:1000. 29 When we compared the prevalence of KC in the FMF group (4%) with the highest prevalence of KC reported in the literature 11 (0.2%), the prevalence of KC in the FMF group (4%) was still statistically significantly higher than that reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…29 When we compared the prevalence of KC in the FMF group (4%) with the highest prevalence of KC reported in the literature 11 (0.2%), the prevalence of KC in the FMF group (4%) was still statistically significantly higher than that reported previously. 11,[24][25][26][27][28] Three patients with KC and FMF had a homozygous mutation (M694V/M694V in 2 cases and M680I/ M680I in 1 case), whereas 1 had a compound heterozygous mutation (M694V/M680I). In the evaluation performed by the FMF study group in Turkey, M694V (51.4%) and M680I (14.4%) were reported to be the most common mutations.…”
Section: Discussionmentioning
confidence: 99%
“…KC occurs in both genders and all ethnicities with higher prevalence and incidence rates in Asians compared with whites. 1,2 A study undertaken in the Midlands area of the United Kingdom found a prevalence of 4:1, and an incidence of 4.4:1 was reported in Asians compared with whites, whereas another UK study conducted in Yorkshire found that the incidence was 7.5 times higher in Asians compared with whites. 3 KC is typically bilateral and is characterized by progressive thinning of the cornea, leading to asymmetric bulging and, in advanced cases, formation of a conical cornea.…”
mentioning
confidence: 94%
“…[5][6][7] The differences seen in the prevalence rates in different studies have been attributed to the impact of environmental factors, race, [8][9][10] and prevalence of concomitant diseases such as eczema, atopy, and asthma. [11][12][13][14][15][16] Reports indicating a higher incidence 17,18 and prevalence [5][6][7] in Asian and Middle Eastern populations have highlighted the need to review it in a population-based study in this area more than ever before.…”
mentioning
confidence: 99%